A comparison of immunotherapy delivery methods for allergen immunotherapy. (May 2013) - Klimek, Ludger; Pfaar, Oliver
Background: Allergic diseases are among the most common diseases in humans. Besides allergen avoidance, allergen-specific immunotherapy is the only causative treatment option. During recent years, many innovations of this therapy have emerged.Methods: Selective literature research in Medline and PubMed, under the inclusion of national and international guidelines and Cochrane meta analyses.Results: In several meta-analyses, the clinical efficacy of subcutaneous immunotherapy (SCIT) has been largely demonstrated. Recently, major research activities in mucosal immunotherapies focused on the sublingual application route. There are well-documented clinical data on the efficacy and safety of this form of immunotherapy. New application routes as well as new immune-modifying agents such as virus-like particles or CpG-motifs have also been investigated.Conclusion: SIT is accepted to be the only causative treatment option for allergies. New application routes and new immune-modifying agents will allow for different delivery methods in the future.